ПОИСК ИСТОЧНИКА И РАЗРАБОТКА СПОСОБОВ ПОЛУЧЕНИЯ БИОСЕНСОРА ДЛЯ ОПРЕДЕЛЕНИЯ ГЛЮТАМАТА (Experimental biology, 2015)
In the laboratory, the structure and regulation of the enzyme was first discovered a new way of glutamate catabolism, carried out previously unknown enzyme complex (FC), consisting of malate dehydrogenase (MDH) and глютаматоксалоацетатаминотрансферазы (GOAT). It is established that FC performs the irreversible oxidation ofmalic acid followed by transamination of oxaloacetic acid formed from glutamate, which leads to the formation of aspartate and 2-oksoglyutarata as end products. The final product is also recovered coenzyme NADH. Reactions catalyzed by FC, allow one side to get energy from malate and the other katabolizirovat glutamate without loss of precious ammonia. And, very importantly, the result is a aspartic acid necessary for the synthesis of purines - the important components of nucleic acid synthesis. The objects of study were the seeds of the cultivar 'glassy - 24. The activity of the enzyme complex was measured for 2-3 minutes. Activity was determined in mM reduced NADH for 1minute per mg protein. The amount of protein was determined by mikrobiuretovym spectrophotometrically at a wavelength of 330 nm. Scheme of purification of the enzyme complex includes the following steps: homogenization, centrifugation, ammonium sulfate precipitation (30-70%), desalting on Sephadex G-50, ion-exchange chromatographyon DEAE cellulose, DE-52.
Keywords: ammonium sulfate; ion-exchange